Needs and Opportunities for Implementing Community Learning Centers in Community Education in South Papua - Anita, Adela; Riyana, Minuk; Tinambunan, Hermanto; Bako, Seven Marganda; Ohee, Gabriel Gloria; Khasanah, Intan Farida (Universitas Negeri Padang, 2025)
This study aims to analyze the needs and opportunities for implementing Community Learning Centers (CLCs) to support the development of community education in South Papua. The existence of CLCs in the region remains limited, despite their crucial role as non-formal learning institutions that can reach communities with diverse social, economic, and cultural backgrounds. This research employs a qualitative approach using interviews, observations, and documentation studies as data collection techniques. Informants include community leaders, educators, government officials, and residents who are the target of community education programs. The findings reveal a significant need for CLC implementation, particularly in literacy eradication, vocational skills improvement, digital literacy, and entrepreneurship development. Furthermore, there are substantial opportunities to establish and expand CLCs through local government support, collaboration with higher education institutions, and partnerships with community organizations. The study concludes that CLCs are an effective strategy to expand access to non-formal education, strengthen community empowerment, and contribute to sustainable development in South Papua.